Access to Care as a Barrier to Mammography for Black Women. (February 2021) - Aleshire, Mollie E.; Adegboyega, Adebola; Escontrías, Omar A.; Edward, Jean; Hatcher, Jennifer
Racial disparities in breast cancer screening, morbidity, and mortality persist for Black women. This study examines Black women's mammography beliefs and experiences with specific focus on barriers to mammography access in an urban city in the South East, United States. This retrospective, qualitative study usedPenchansky and Thomas' conceptualization of health care access as the framework for the data analysis. In-depth, semistructured interviews were conducted with 39 Black women. Structural and personal factors continue to create barriers to mammography among Black women. Barriers to mammography were identified for each of the Penchansky and Thomas five dimensions of access to care: accessibility, affordability, availability, accommodation, and acceptability. Clinical practice strategies to increase mammography screening in Black women must be multifactorial, patient-centered, and culturally congruent. Policy development must address the structural barriers to mammography screening through expansion of health insurance coverage and increased accessibility to health care.